Explaining voter turnout: A meta-analysis of national and subnational elections. (June 2016) - Cancela, João; Geys, Benny
Abstract: Research about voter turnout has expanded rapidly in recent years. This article takes stock of this development by extending the meta-analysis of Geys (2006) in two main ways. First, we add 102 studies published between 2002 and 2015 to the initial sample of 83 studies. Overall, we document only minor changes to the original inferences. Second, since different processes might conceivably play at different levels of government, we exploit the larger sample to separately analyse the determinants of voter turnout in national versus subnational elections. We find that campaign expenditures, election closeness and registration requirements have more explanatory power in national elections, whereas population size and composition, concurrent elections, and the electoral system play a more important role for explaining turnout in subnational elections. Highlights: We expand the meta-analysis ofGeys (2006) with 102 articles to cover 185 articles. We broadly confirm the original findings in our more diverse pool of studies. We extend the analysis to a comparative study of national vs. subnational elections. The explanatory power of distinct covariates is found to vary across types of elections. Future work should attend more closely to the territorial scope of the election.